2006
DOI: 10.1007/s00894-006-0150-y
|View full text |Cite
|
Sign up to set email alerts
|

A hydrophobic similarity analysis of solvation effects on nucleic acid bases

Abstract: We investigate the changes in the solvation properties of the natural nucleic acid bases due to the formation of the canonical Watson-Crick hydrogen-bonded complexes. To this end, the changes in the free energy of solvation of the bases induced upon hydrogen-bonded dimerization are analyzed by means of the hydrophobic similarity index, which relies on the atomic contributions to the free energy of solvation determined by the partitioning method implemented in the framework of the MST continuum model. Such an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 65 publications
1
9
0
Order By: Relevance
“…For d w < 0.9 nm, dAMP, dCMP, and dTMP had minima in θ for both adsorption and desorption, indicating that the sugar adsorbed after the nucleobase and desorbed before the nucleobase. The magnitude of the minima of θ followed the order dCMP < dAMP < dTMP, which was consistent with the order of hydrophobicity of their nucleobases. , For d w < 0.9 nm, dGMP had a maximum in θ for both adsorption and desorption, indicating that the sugar adsorbed before the nucleobase and desorbed after the nucleobase. The different behavior of dGMP was likely because its nucleobase was the least hydrophobic. , The adsorption and desorption curves for each type of dNMP were similar to each other which indicated that adsorption and desorption occurred in a similar way.…”
Section: Results and Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…For d w < 0.9 nm, dAMP, dCMP, and dTMP had minima in θ for both adsorption and desorption, indicating that the sugar adsorbed after the nucleobase and desorbed before the nucleobase. The magnitude of the minima of θ followed the order dCMP < dAMP < dTMP, which was consistent with the order of hydrophobicity of their nucleobases. , For d w < 0.9 nm, dGMP had a maximum in θ for both adsorption and desorption, indicating that the sugar adsorbed before the nucleobase and desorbed after the nucleobase. The different behavior of dGMP was likely because its nucleobase was the least hydrophobic. , The adsorption and desorption curves for each type of dNMP were similar to each other which indicated that adsorption and desorption occurred in a similar way.…”
Section: Results and Discussionsupporting
confidence: 70%
“…The different behavior of dGMP was likely because its nucleobase was the least hydrophobic. 67, 68 The adsorption and desorption curves for each type of dNMP were similar to each other which indicated that adsorption and desorption occurred in a similar way.…”
Section: Thementioning
confidence: 75%
See 1 more Smart Citation
“…QM-based continuum solvation methods are a promising strategy for deriving 3D descriptors, such as COSMO-RS-based σ-profiles [78][79][80][81] or MST-derived 3D lipophilicity patterns [82][83][84][97][98][99], which in turn may be exploited in computer-aided drug design. The set of studies reported up to now for a variety of benchmark datasets, covering both measurements of molecular similarity for aligned compound or the derivation of 3D-QSAR models, are encouraging.…”
Section: Final Consideration and Perspectivesmentioning
confidence: 99%
“…In this work, following our previous studies on hydrophobic similarity, the QM/MST‐based hydrophobic contributions have been utilized as physicochemical descriptors suitable for 3D‐QSAR studies. By combining the electrostatic and nonelectrostatic components of the octanol/water partition coefficient, which can obtained through a suitable partitioning of the solvation free energy, the 3D‐QSAR models derived for the five molecular systems have a predictive accuracy that compares well with standard CoMFA and CoMSIA techniques.…”
Section: Final Remarksmentioning
confidence: 99%